Evaluation of The Effectiveness of Ultraviolet Radiation and Reishi Mushroom Extract in Preserving Locally Produced Fruits From Fungal Contamination - Al-Dulaimi, Fahad K.Y. (American Journal of Botany and Bioengineering, 2025)
Fungal contamination is considered one of the most critical factors limiting the quality and shelf life of fresh fruits during storage and marketing. The present study aimed to evaluate the effectiveness of ultraviolet-C radiation (UV-C) and the extract of the medicinal mushroom Ganoderma lucidum (Reishi) in suppressing pathogenic fungal isolates associated with Iraqi white apple (Malus domestica), orange (Citrus sinensis), and peach (Prunus persica), as well as in maintaining their postharvest quality attributes. Fruits were collected, and the associated fungi were isolated and identified under laboratory conditions. The samples were subsequently exposed to different treatments: UV-C (5, 10, and 15 min), Reishi extract (25, 50, and 100 mg/ml), and a combined treatment (UV-C10 + Reishi 50). Evaluations included the incubation period until the appearance of first visible symptoms, infection incidence at 7 and 14 days, and several quality indicators such as weight loss, firmness, color parameters (L*, a*, b*), chlorophyll or anthocyanin content, total soluble solids (TSS), and titratable acidity (TA). Isolation and identification results revealed that Penicillium expansum was the most frequent isolate in Iraqi white apple, Penicillium digitatum predominated in orange, whereas Monilinia fructicola was dominant in peach. The combined treatment (UV-C10 + Reishi 50) proved to be the most effective, extending the incubation period to 15 days compared with only 3 days in the untreated control, and reducing infection incidence to as low as 3% after 14 days. Moreover, this treatment minimized weight loss (4.8% in orange and 8.0% in peach), enhanced firmness (36.0 N in orange and 26.0 N in peach), improved color stability, and increased pigment retention, while maintaining TSS and TA within desirable levels. These findings demonstrate that the integration of UV-C radiation with natural fungal extracts provides a sustainable and eco-friendly approach for managing postharvest fungal contamination, extending fruit shelf life, reducing reliance on synthetic fungicides, and supporting the goals of sustainable agriculture.